Baclofen‐induced Tourette‐like Syndrome: tics and echolalia. Issue 2 (4th September 2017) - Yu, Jessica; Ooi, E‐Lin
Summary: We describe an elderly patient who developed a "Tourette like" syndrome after baclofen was administered. A total of 40 mg baclofen was administered over thirty‐six hours to relieve pain following a fall. She became unconscious and subsequently developed muscle tics and echolalia. Two days later she recovered fully and was discharged from hospital after two weeks of rehabilitation.